Ethical challenges in conducting research in low and middle income setting during public health emergencies: a qualitative evidence of a COVID-19 pandemic: the experience of Iran - Ehsan Shamsi-Gooshki (BMC Medical Ethics, 2025)
Abstract Background Every minute during an epidemic is important and research in such conditions is for the benefit of the society. Considering that identifying experiences is a way to prevent repeated mistakes and prepare people to face crisis situations, this study aimed to explain participants’ experiences of ethical challenges encountered in conducting research related to Covid-19 in Iran. Method This qualitative study was carried out using conventional content analysis for 2 years from March 2020 to March 2022 in Tehran, Iran. A number of 30 people were selected in a purposeful method and information was obtained through semi-structured interviews. The participants in the study were people with positions including members of institutional and national research ethics committees, researchers, clinicians, university hospitals managers during the COVID-19 pandemic. The method of data analysis in this study was conventional content analysis using the Graneheim and Lundman method. Results Participants’ experiences on ethical challenges were explained through three themes: “substantive ethical values principles”, “the Research Environment”, “Research Governance and Management”. Conclusion This study examines ethical challenges in COVID-19 research across three domains: values, environment, and research governance. The results suggest the need to develop crisis-specific ethical frameworks, strengthen research ethics infrastructure and training, and establish more transparent standards and oversight systems. These findings could be useful in refining ethical policies and managing future crises.